Direct in vivo reprogramming with non-viral sequential targeting nanoparticles promotes cardiac regeneration. (September 2021) - Wang, Qiaozi; Song, Yanan; Chen, Jing; Li, Qiyu; Gao, Jinfeng; Tan, Haipeng; Zhu, Yuefei; Wang, Zhengmin; Li, Minghui; Yang, Hongbo; Zhang, Ning; Li, Xiaomin; et al.
Abstract: microRNA-mediated direct cardiac reprogramming, directly converts fibroblasts into induced cardiomyocyte-like cells (iCMs), which holds great promise in cardiac regeneration therapy. However, effective approaches to deliver therapeutic microRNA into cardiac fibroblasts (CFs) to induce in vivo cardiac reprogramming remain to be explored. Herein, a non-viral biomimetic system to directly reprogram CFs for cardiac regeneration after myocardial injury was developed by coating FH peptide-modified neutrophil-mimicking membranes on mesoporous silicon nanoparticles (MSNs) loaded with microRNA1, 133, 208, and 499 (miR Combo). Through utilizing the natural inflammation-homing ability of neutrophil membrane protein and FH peptide's high affinity to tenascin-C (TN-C) produced by CFs, this nanoparticle could realize sequential targeting to CFs in the injured heart and precise intracellular delivery of miRCombo, which induced reprogramming resident CFs into iCMs. In a mouse model of myocardial ischemia/reperfusion injury, intravenous injection of the nanoparticles successfully delivered miRCombo into fibroblasts and led to efficient reprogramming, resulting in improved cardiac function and attenuated fibrosis. This delivery system is minimally invasive and bio-safe, providing a proof-of-concept for biomimetic and sequential targeting nanomedicine delivery system for microRNA-mediated reprogramming therapy in multiple diseases.